2020
DOI: 10.1590/0103-8478cr20200012
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of ultrasound-assisted optimized process of high purity rice bran protein extraction

Abstract: Rice bran is a by-product of the rice milling process, found worldwide in abundance and highlighted due its protein content. This study optimized the conditions for ultrasonic-assisted extraction of protein from defatted rice bran (DRB) and characterized the rice bran protein concentrate (RBPC). A sequential strategy of experimental design was employed; the effect of pH, temperature, ultrasound exposure time, and amplitude were evaluated regarding the percentage of protein extraction by a Full factorial design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The defatted rice bran protein was extracted by ultrasound‐assisted extraction at two different frequencies: 37 and 80 kHz. The maximum protein yield was recovered at a lower frequency (15.07%) 43 . A similar pattern of results was seen in ultrasound‐assisted extraction of watermelon seed protein.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The defatted rice bran protein was extracted by ultrasound‐assisted extraction at two different frequencies: 37 and 80 kHz. The maximum protein yield was recovered at a lower frequency (15.07%) 43 . A similar pattern of results was seen in ultrasound‐assisted extraction of watermelon seed protein.…”
Section: Resultssupporting
confidence: 77%
“…The maximum protein yield was recovered at a lower frequency (15.07%). 43 A similar pattern of results was seen in ultrasound-assisted extraction of watermelon seed protein. A higher protein yield of 87% was obtained at ultrasound power of 90 W), frequency 25 kHz, and duty cycle 75%.…”
Section: Determination Of Effectivity Of Ultrasound Processsupporting
confidence: 63%
“…The cavitational shear force generated during ultrasonication can destroy the non-covalent bonds (such as hydrogen bonds and hydrophobic bonds) between protein molecules or within the molecules, so that the compact structure of protein aggregates is opened, and the particle size is reduced to improve extraction rate. 24,25 Zhao et al 26 used ultrasonic-assisted extraction of Dolichos lablab L. protein (DLP), and found that the particle size of DLP was significantly smaller and the extraction rate significantly improved compared to traditional extraction methods. Wang et al 27 also found that the particle size of pea protein extracted by ultrasonic-assisted extraction was significantly smaller, and the biological activity of the extracted protein was also significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound is widely used as a green, safe and reliable technology. The cavitational shear force generated during ultrasonication can destroy the non‐covalent bonds (such as hydrogen bonds and hydrophobic bonds) between protein molecules or within the molecules, so that the compact structure of protein aggregates is opened, and the particle size is reduced to improve extraction rate 24,25 . Zhao et al 26 .…”
Section: Introductionmentioning
confidence: 99%